Bioengineering a Multicomponent Spinal Motion Segment Construct—A 3D Model for Complex Tissue Engineering. Issue 1 (20th May 2014) - Chik, Tsz Kit; Chooi, Wai Hon; Li, Yuk Yin; Ho, Fu Chak; Cheng, Hiu Wa; Choy, Tsz Hang; Sze, Kam Yim; Luk, Keith Kei Dip; Cheung, Kenneth Man Chi; Chan, Barbara Pui
<x xml:space="preserve">Abstract</x> Intervertebral disc degeneration is an important clinical problem but existing treatments have significant drawbacks. The ability to bioengineer the entire spinal motion segment (SMS) offers hope for better motion preservation strategies but is extremely challenging. Here, fabrication of a multicomponent SMS construct with complex hierarchical organization from mesenchymal stem cells and collagen‐based biomaterials, using a module‐based integrative approach, is reported. The construct consists of two osteochondral subunits, a nucleus pulposus (NP‐)‐like core and a multi‐lamellae annulus fibrosus (AF‐)‐like component. Chondrogenic medium is crucial for stabilizing the osteochondral subunits, which are shown to allow passive nutrient diffusion, while cyclic compression is necessary for better fiber matrix organization. Cells adhere, survive, and interact with the NP‐like core. Cyclic torsional loading stimulates cell alignment in the AF‐like lamellae and the number of lamellae affects the mechanical properties of the construct. This work represents an important milestone in SMS tissue engineering and provides a 3D model for studying tissue maturation and functional remodeling.